Generic water-based spray-assisted growth for scalable high-efficiency carbon-electrode all-inorganic perovskite solar cells - Zeyang Zhang (Elsevier, 2021)
Summary: A water-based spray-assisted growth strategy is proposed to prepare large-area all-inorganic perovskite films for perovskite solar cells (PSCs), which involves in spraying of cesium halide water solution onto spin-coating-deposited lead halide films, followed by thermal annealing. With CsPbBr3 as an example, we show that as-proposed growth strategy can enable the films with uniform surface, full coverage, pure phase, large grains, and high crystallinity, which primarily benefits from the controllable CsBr loading quantity, and the use of water as CsBr solvent makes the reaction between CsBr and PbBr2 immune to PbBr2 film microstructure. As a result, the small-area (0.09 cm2) and large-area (1.00 cm2) carbon-electrode CsPbBr3 PSCs yield the record-high efficiencies of 10.22% and 8.21%, respectively, coupled with excellent operational stability. We also illustrate that the water-based spray-assisted deposition strategy is suitable to prepare CsPbCl3, CsPbIBr2, and CsPbI2Br films with outstanding efficiencies of 1.27%, 10.44%, and 13.30%, respectively, for carbon-electrode PSCs.